Local Farmers’ Perceptions about Covid-19 Impact on Agriculture: Case of Selected Rural Areas in Ekiti State, Nigeria - Oloruntimilehin Sola Ojo; Oluwasanmi Oyedeji; Ebenezer Toyin Megbowon (Borong Newinera Publisher, 2022)
The outbreak of the Corona virus that ravaged most parts of the globe including Nigeria had impacted all sectors in all economies. Understanding the perception of rural farmers about Covid-19 pandemic impacts on agricultural activities becomes imperative as it will help local government authorities identify possible vulnerabilities and prioritize interventions. This study therefore seeks 1) to know farmer perceptions of the probable impacts of Covid-19 pandemic on agricultural production process of rural farmers and 2) to examine if this perception varies by the population subgroups of farmers? Using selected rural areas in five local government areas in Ekiti state as case study, primary data obtained through the administered questionnaire were analysed using descriptive statistics and analysis of variance. Results indicated that the two most potential and identified possible vulnerabilities are agricultural output and access to finance, and income with respect to production process and welfare, respectively. ANOVA results indicated that both age and gender are not statistically significant at 5 percent in explaining perceived impact of covid-19 on agricultural output likewise others such as educational attainment, years of farming experience and marital status. Hence, none of the levels in each of the chosen categorical variables is found to be statistically different from the other ones in impacting agricultural production. It is therefore recommended that government policies aimed at stimulating agricultural production should not be gender bias and age driven. Similarly, other factors such as years of farming experience, educational attainment and marital status should be de-emphasized when initiating such policies.